Regulatory Role of Silicon on Growth, Potassium Uptake, Ionic Homeostasis, Proline Accumulation, and Antioxidant Capacity of Soybean Plants Under Salt Stress - Peña Calzada, Kolima [UNESP] (2023)
In this study, we investigated the regulatory roles of different vias of silicon (Si) applications on soybean biochemical, physiological, and growth responses and their effectiveness in salt stress remediation. The key mechanisms for improving growth and potassium (K+), ion homeostasis, proline content, and the enzymatic antioxidant capacity of salt-affected soybean plants (50 and 100 mmol NaCl L−1) were investigated when potassium silicate was supplied in different vias (non-Si application, foliar spraying at 20 mmol L−1, nutrient solution addition at 2.0 mmol L−1, and co-application of foliar spraying at 20 mmol L−1 and nutrient solution addition at 2.0 mmol L−1). Salt stress sharply decreased soybean growth by increasing Na+ uptake and lipid peroxidation (LPO) content in the roots and leaves. Alternatively, soybean growth, K+/Na+ ratio, proline content, and enzymatic antioxidant activity were reduced under moderate and high salinity conditions. However, different vias of Si application increased soybean tolerance to salinity stress by drastically decreasing Na+ uptake and LPO concentration, increasing K+ concentration, K+/Na+ ratio, and proline accumulation, upregulating enzymatic antioxidant activity, and increasing plant growth. As compared to other exogenous application methods, co-application foliar spraying with a nutrient solution of Si produced enhanced results. Furthermore, foliar spraying of Si is an efficient method for salt stress remediation. The present study indicated that Si improved soybean growth by enhancing K+ and proline content, and that antioxidant capacity could be used as a mitigation strategy against salinity stress-related damages.